Influence of Pixel Size Difference on Imaging Plate Computed Radiography on the Quality of Digital Images in Intraoral Dental Radiography Examination - Sismadi, Adi; Rianto, Sugeng; Abimanyu, Bagus (Journal of World Science, 2023)
This research aims to determine the assessment of digital image quality from 18 x 24 cm Imaging Plates of the ST (Standard) and HR (High-Resolution) types by engineering the dimensions on intraoral dental radiographic examinations so that we can determine the differences in image quality for each type of imaging. Plate Computed Radiography. The research method took the form of an experiment using the subjective quality assessment method of digital images in intraoral dental radiographic examinations using the object of patients who carried out the examination and brought a referral letter for 60 patients. Analyze image quality by measuring MSE (Mean et al.), PSNR (Peak Signal to Noise) and PIQE (Perception-based Image Quality Evaluator) score. The results of the research show that the analysis of differences in IP FCR ST and HR types with the Mann-Whitney Test shows the significance values of all digital images (< 0.05), namely: MSE (0.041), PSNR (0.041), PIQE score (0.012), meaning that there is a difference in digital image quality between IP FCR ST and HR, while with subjective analysis the respondents gave IP FCR HR results of 57.14% and IP FCR ST 42.86%. The difference in the results of the two types shows that IP FCR HR can be used as the main alternative in selecting IP FCR in intraoral dental radiographic examinations).